Disinformation in open online media : first Multidisciplinary International Symposium, MISDOOM 2019, Hamburg, Germany, February 27-March 1, 2019, Revised selected papers /: first Multidisciplinary International Symposium, MISDOOM 2019, Hamburg, Germany, February 27-March 1, 2019, Revised selected papers. (2020) - Unknown
No abstract available